Rancang Bangun Aplikasi Penilaian Dan Evaluasi Kinerja Pegawai Menggunakan Metode Key Performance Indicators Pada Dinas Pendidikan Kabupaten Sampang - Pratama, Fahrizal Fauzi; Setiawan, Henry Bambang; Rahmawati, Endra (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
Education offices at kabupaten sampang madura islands is a institution responsible for on the process academic of the - the agency to the education system in the kabupaten sampang.Work principal and routine day-to-day that is as the agency that administers the educational process done by officials.Among the job is to organize a database institutions - the agency to the education system in it, as admit data, proceeds it and make a report how many schools that are needed and managed.With the tasks many heads government offices must control any performance city official vision, the mission and the purpose company reached.The district education office sampang has some constraints to the process performance evaluation of employees as head of difficulty on the monitoring of the performance employees , the evaluation process that takes time , the assessment results of the not conforming because error input calculations use ms.excel so that assessment the employee not in accordance with of performance and difficulty evaluate the performance of his servants.From trouble was needed application assessment and performance evaluation employees with the methods key performance indicators based on the companys policy so the to simplify the evaluation process performance employees and simplify evaluate the performance of each employee.